Business House as an Entrepreneurship Education Program to Boost Entrepreneurship Intention Amongst Student University in Indonesia - Wahjono, Sentot Imam; Marina , Anna; Fen, Fam Soo (Advances in Social Sciences Research Journal, 2019)
By applying the theory of planned behavior, which is the attitude, subjective norms, and behavior control perceived, this study discusses the influence of the Business House as an Entrepreneurship Education Program to increase the intention of university students in entrepreneurship. A quantitative approach was chosen for this research. The study was conducted at Universitas Muhammadiyah Surabaya Indonesia (UMSurabaya). The unit analysis was 480 students who had taken courses in Introduction to Business. Using the Krejcie Morgan table with an error rate of 5%, the sample is 202, after being collected again with google form complete data was obtained to be analyzed with SPSS of 190 respondents. The data analysis used includes descriptive analysis and path analysis. The findings of this research found evidence that attitude, subjective norms and perceived behavior control have a positive and significant influence on student entrepreneurial intention by being mediated by entrepreneurial education programs in the form of business house activities. The findings of this study imply that entrepreneurship education program activities are needed in the lectures of business students as entrepreneurial education programs to strengthen student intentions in family business knowledge. This implication is very important especially applied in universities that expect graduates to do business.